The Student’s Errors in Writing Descriptive Text at Seventh Grade Students of Junior High School Laboratorium Jambi City - F. Margaretta Siagian; Yanti Ismiyati; Ridho Praja Dinata (Universitas Batanghari Jambi, 2022)
The purpose of conducting this research is to know the student’s errors in writting descriptive text at seventh grade of SMP Laboratorium Jambi City. The research design of this research is quantitative with descriptive approach. The method used in this study is a qualitative description. Fifteen seventh-grade junior high school students were the subjects in this study. The population of this research are 10 students and research used total sampling technique. The data of this research were collected through the test. The data were analyzed by using descriptive quantitative. The result showed that the seventh grade of SMP Laboratorium Jambi City, there are still some mistakes in writing descriptive texts about people, animals, and objects.